Maternal Perception of COVID-19's Potential Impact on the Development of Children Born During the Pandemic - Laughlin, Emma; Clinch, Caroline; Ballback, Rachel; Ghulmi, Lima; Hilton, Claudia (Journal of Maternal and Child Health, 2024)
Background: COVID-19 impacted the world population through isolation and social distancing recommendations, which affected new mothers’ participation in social interactions. Social interaction is a critical aspect of child development that was limited due to the COVID-19 pandemic. This study aimed to answer the question, “What are the maternal perceptions of the potential impact of social measures during the COVID-19 pandemic on the development of children born during the pandemic?”             Subjects and Method: This qualitative research is important to explore the potential impact of COVID-19 on the maternal perception of child development during the pandemic. Five online interviews were conducted with mothers who gave birth to their first child between March 2020 and March 2021. Open, axial, and selective coding were utilized to identify relevant themes. Results: Participants felt gross and fine motor skills, cognition, and socioemotional skills were not impacted by COVID-19, but there was a perceived impact on language and communication skills. Conclusion: The perceived decrease in language and communication skills due to social distancing measures of COVID-19 was congruent with the initial hypothesis: “Delayed language and communication skills are a concern identified by mothers of children born during the pandemic”.